Management of patients with atopic dermatitis undergoing systemic therapy during COVID‐19 pandemic in Italy: Data from the DA‐COVID‐19 registry. Issue 6 (9th March 2021) - Chiricozzi, Andrea; Talamonti, Marina; De Simone, Clara; Galluzzo, Marco; Gori, Niccolò; Fabbrocini, Gabriella; Marzano, Angelo Valerio; Girolomoni, Giampiero; Offidani, Annamaria; Rossi, Maria Teresa; Bianchi, Luca; Cristaudo, Antonio; et al.
Abstract: Background: Few and small studies have described the management of immunomodulant/immunosuppressive therapies or phototherapy in atopic dermatitis (AD) patients during coronavirus disease 2019 (COVID‐19) pandemic. Methods: A national registry, named DA‐COVID‐19 and involving 35 Italian dermatology units, was established in order to evaluate the impact of COVID‐19 pandemic on the management of adult AD patients treated with systemic immunomodulant/immunosuppressive medications or phototherapy. Demographic and clinical data were obtained at different timepoints by teledermatology during COVID‐19 pandemic, when regular visits were not allowed due to sanitary restrictions. Disease severity was assessed by both physician‐ and patient‐reported assessment scores evaluating itch intensity, sleep disturbances, and AD severity. Results: A total of 1831 patients were included, with 1580/1831 (86.3%) continuing therapy during pandemic. Most patients were treated with dupilumab (86.1%, 1576/1831) that was interrupted in only 9.9% (156/1576) of cases, while systemic immunosuppressive compounds were more frequently withdrawn. Treatment interruption was due to decision of the patient, general practitioner, or dermatologist in 39.9% (114/286), 5.6% (16/286), and 30.1% (86/286) of cases, respectively. Fear of increased susceptibility to SARS‐CoV‐2 infection (24.8%, 71/286) was one of the main causes of interruption. Sixteen patients (0.9%) resulted positive to SARS‐CoV‐2 infection; 3 of them (0.2%) were hospitalized but no cases of COVID‐related death occurred. Conclusions: Most AD patients continued systemic treatments during COVID pandemic and lockdown period, without high impact on disease control, particularly dupilumab‐treated patients. Abstract : Among 1831 studied AD patients, 86.1% were treated with dupilumab. Patients continuing therapy experienced a marked reduction of disease severity during pandemic. The causes of treatment interruption included: fear of increased susceptibility to SARS‐CoV‐2 infection (24.8%), occurrence of comorbidities (5.9%), age above 60 years (5.2%), SARS‐CoV‐2 infection (2.8%), close contact with SARS‐CoV‐2‐positive subject (2.4%), other reasons, for example, inability to maintain drug supply, non‐medical/unspecified causes (58.7%). Abbreviations: AD, atopic dermatitis; COVID‐19: coronavirus disease 2019; EASI, eczema area severity index; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus type 2.